Some Are Victims and Some Are Lost: Contested Statuses of War Victims in Croatia - Kardov, Kruno (2007)
Every transitional society that is faced with violent past goes through a process of destabilisation of previously established certainties and identity structures. Facts and past events that were once denied or excluded from dominant historical narratives are getting legitimacy in wider society and sometimes even offical recognition by the state. But such acknowledgment is not necessearly followed by the change in position of the victims in society or the visibility of the victims in the public arena. Although seemingly causally related these two spheres can be maintained separate due to complex processes of negation, displacement of perspectives, and attribution of moral values to the victims. The author will present results of a survey reserch that illustrate these problems in Croatia. The research was organized by Documenta-Centre for Dealing with the Past and carried out by Puls public opinion research agency in 2006 on a representative sample of Croatia's majority population (N=700), and two additional samples of Serbs (N=150) and Croats (N=150) from war-torn region
Projekt MZOS
ENG